Nota técnica 1: Transmisión eléctrica y la "ley corta": una nota sobre riesgo y la tasa de descuento " - Galetovic, Alexander (Estudios de Economía, 2016)
This paper studies the determinant of the appropriate rate to fix transmission tolls. I develop a simple model that allows to decompose it in the sum of the risk-free rate and a risk premium. There are two general principles with vhich the rate should conform: (a) it should vary pari passu with the risk-free rate (b) it should compensate the transmission company for: (i) the “risk of regulatory opportunism”; (ii) the nondiversifiable risk imposed to the transmission company by the price-fixing rule; (iii) and also add a liquidity premium. Legislation presently discussed in congress, however, would grant a fixed 10% real rate to the transmission company. Approximating the risk-free rate by the rate paid by a 20-year b ond issued by the Central Bank (PRC) I use the model to estimate the level of risk that justifies a rate of exactly 10%. Finally, I propose a method to regulate transmission fees that would eliminate most revenue risk and would avoid a need to fix a regulated rate.